2006
DOI: 10.1021/jo060643i
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of 4,5-Epoxy-9-trimethylsilyldecalines. Application to the Synthesis of the Natural Eremophilane (−)-Aristolochene

Abstract: Several 4,5-epoxy-9-trimethylsilyl-eudesmanes and 15-nor-eudesmanes, having different relative stereochemistry and substitution at the oxirane ring, have been prepared starting from (-)-carvone and subjected to acid-promoted rearrangement. The presence of the silicon at C9 favors two different main reaction pathways involving C14-methyl or C1-methylene migration through the stabilization of a C10 carbocation intermediate. Selective 1,2-migration of the bridgehead methyl group takes place with trisubstituted be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Treatmentw ith TiF 4 resulted in epoxide opening with methyl group migration and cleavage of the trimethylsilyl cation to produce 86,t hat was defunctionalised in two more steps to 70. [193] Compound 70 was also reported as as ide product of valencenesynthase from V. vinifera [150] and as aheadspace constituentf rom Streptomyces acidiscabies. [194] Both compounds (+ +)-68 and (À)-70 are present in extracts from the liverwort Dumortiera hirsuta with absolute configurations established in comparison to authentic standards by GC using ac hiral sta-tionary phase.…”
Section: Rearranged Eudesmanes From H1mentioning
confidence: 99%
“…Treatmentw ith TiF 4 resulted in epoxide opening with methyl group migration and cleavage of the trimethylsilyl cation to produce 86,t hat was defunctionalised in two more steps to 70. [193] Compound 70 was also reported as as ide product of valencenesynthase from V. vinifera [150] and as aheadspace constituentf rom Streptomyces acidiscabies. [194] Both compounds (+ +)-68 and (À)-70 are present in extracts from the liverwort Dumortiera hirsuta with absolute configurations established in comparison to authentic standards by GC using ac hiral sta-tionary phase.…”
Section: Rearranged Eudesmanes From H1mentioning
confidence: 99%
“…35 The acid-catalysed conversion of de isotwistanol skeleton to the tricyclo[5.2.1.0 4,8 ]decane skeleton has provided support for the proposed biosynthesis of allopupukeananes from pupukeananes. The presence of the silicon at C(9) favours two different main reaction pathways involving bridgehead-methyl or C(1)-methylene migration through the stabilization of a carbocation intermediate.…”
Section: Cationic Rearrangementsmentioning
confidence: 96%
“…Metal alkoxides, such as sodium benzylate, in catalytic amounts promote the [2,3]-Wittig rearrangement of silyl enolates (34), to afford the corresponding rearrangement product (35) in good yields at room temperature (Scheme 8). 23 It has been demonstrated that the oxygen anion of initially formed product (36) effectively catalysed the [2,3]-Wittig rearrangement as a Lewis base.…”
Section: Anionic Rearrangementsmentioning
confidence: 99%
“…Acid-catalysed reactions of 4,5-epoxy-9-trimethylsilyleudesmanes results in rearrangement products determined by the stabilization of the rearranged carbocation by the silicon at its β-position. 186 With the aid of deuterium labelling, mechanisms of the reactions of methylenecyclopropanes with aldehydes in the presence of BF 3 .OEt 2 were addressed, with several carbocations proposed as intermediates. 187 …”
Section: Carbocations In Synthesismentioning
confidence: 99%